“I’ma put the lil homies on next”: mixtape methodology and mapping Black men’s college experiences - Livingston, Donovan Albert (Frontiers in Education, 2024)
In recent years, many studies have attempted to explore the experiences of historically marginalized populations within higher education; especially Black men. While most studies expand the discourse about the Black male experience in higher education, few incorporate arts-based methodologies that uniquely speak to the cultural sensibilities of Black men. This study remixes traditional qualitative methodologies through an arts-informed, hip-hop pedagogical perspective by inviting participants to write and record original music in response to a prompt related to an original research question: What does the creation of a Hip-Hop mixtape by Black, male, college-educated emcees, reveal about Black men's experiences in higher education? Together, this curated collection of songs formed a mixtape, which was made available across multiple streaming platforms, and introducing the counternarratives of Black male hip-hop collegians to audiences beyond the academy. The resulting mixtape offers practical implications for revolutionizing the way educators' may center cultural knowledge as means of collecting data that captures the nuance of marginalized students' experiences within (and beyond) the context of school.